2011
DOI: 10.1097/ta.0b013e318228842e
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary, Histologic, and Inflammatory Effects of Intravenous Na2S After Blunt Chest Trauma-Induced Lung Contusion in Mice

Abstract: Posttreatment sulfide infusion after blunt chest trauma did not affect the impaired lung mechanics and gas exchange but attenuated stress protein expression and apoptotic cell death. This protective effect was amplified by moderate hypothermia. The simultaneous reduction in cystathionine-β synthase and cystathionine-γ lyase expression supports the role of H2S-generating enzymes as an adaptive response during stress states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 33 publications
4
58
0
Order By: Relevance
“…To reduce the number of animals needed, as requested by the regulations for animal protection, data from sham animals after 12 (n = 6) and 24 h (n = 7) were pooled after exclusion of statistically significant differences in both sham groups. Blunt chest trauma was induced by a single blast wave centered on the thorax as previously described (3,10). In brief, compressed air rapidly ruptured a Mylar polyester film (Du Pont de Nemur, Bad Homburg, Germany), which released a reproducible single blast wave toward the animal's midsternal chest and thus induced a reproducible contusion of the lungs without any direct impact on visceral organs.…”
Section: Anesthesia Blast Wave and Experimental Protocolmentioning
confidence: 99%
See 3 more Smart Citations
“…To reduce the number of animals needed, as requested by the regulations for animal protection, data from sham animals after 12 (n = 6) and 24 h (n = 7) were pooled after exclusion of statistically significant differences in both sham groups. Blunt chest trauma was induced by a single blast wave centered on the thorax as previously described (3,10). In brief, compressed air rapidly ruptured a Mylar polyester film (Du Pont de Nemur, Bad Homburg, Germany), which released a reproducible single blast wave toward the animal's midsternal chest and thus induced a reproducible contusion of the lungs without any direct impact on visceral organs.…”
Section: Anesthesia Blast Wave and Experimental Protocolmentioning
confidence: 99%
“…For this purpose, the trachea of the mice was intubated by tracheotomy immediately postmortem with an 18-gauge cannula, and the lungs were mechanically ventilated with a pressurecontrolled lung-protective ventilation strategy using the flexiVent ventilator. After a lung recruitment maneuver, quasi-static compliance was measured by incrementally increasing the airway pressure up to a maximum inspiratory pressure of 20 cmH 2 O and using the indwelling software of the respirator that allows automatic recording of the inspiratory and expiratory pressure-volume loop (10,11). Airway resistance was measured using a 1-s sinusoidal (singlefrequency) forced oscillation waveform, with an oscillation frequency of 2.5 Hz according to a respiratory rate of 150 breaths/min.…”
Section: Pulmonary Mechanicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhaling H 2 S prior to myocardial ischemia at concentrations that had no metabolic depressant eff ect (10 ppm) attenuated organ damage, but to a lesser degree than concentrations that reduced energy expenditure (100 ppm) [12], suggesting that hypometabolism may indeed enhance the organ-protective properties of H 2 S. Of note, in that study as well as in others demonstrating H 2 S-related organ production coinciding with reduced metabolic activity, hypothermia was prevented [5], [7], [9], [14], [15] in order to elucidate the impact of a simultaneous drop in core temperature. Moreover, organ protection and improved survival were also shown to be in part [12], [13], [15], [34], [35] or even completely [8], [11], [36], [37] independent of any H 2 Sinduced metabolic depression at all. Finally, data obtained in large animal (swine or sheep) models of shock resulting from ischemia/reperfusion [29], [38]- [42], hemorrhage and resuscitation [30], or burn injury [36] also suggested that the benefi cial eff ects of infusing Na 2 S were at least in part independent of metabolic depression and/or a fall in core temperature.…”
Section: Hypothermiamentioning
confidence: 99%